Predictive Factors for Delivery within 7 Days after Successful 48-Hour Treatment of Threatened Preterm Labor - Carolien Roos; Ewoud Schuit; Hubertina C. J. Scheepers; Kitty W. M. Bloemenkamp; Antoinette C. Bolte; Hans J. J. Duvekot; Jim van Eyck; Joke H. Kok; Anneke Kwee; Ashley E. R. Merién; Brent C. Opmeer; Martijn A. Oudijk; et al. (Thieme Medical Publishers, Inc., 2015)
Abstract Objective The aim of this study was to assess which characteristics and results of vaginal examination are predictive for delivery within 7 days, in women with threatened preterm labor after initial treatment. Study Design A secondary analysis of a randomized controlled trial on maintenance nifedipine includes women who remained undelivered after threatened preterm labor for 48 hours. We developed one model for women with premature prelabor rupture of membranes (PPROM) and one without PPROM. The predictors were identified by backward selection. We assessed calibration and discrimination and used bootstrapping techniques to correct for potential overfitting. Results For women with PPROM (model 1), nulliparity, history of preterm birth, and vaginal bleeding were included in the multivariable analysis. For women without PPROM (model 2), maternal age, vaginal bleeding, cervical length, and fetal fibronectin (fFN) status were in the multivariable analysis. Discriminative capability was moderate to good (c-statistic 0.68; 95% confidence interval [CI] 0.60-0.77 for model 1 and 0.89; 95% CI, 0.84-0.93 for model 2). Conclusion PPROM and vaginal bleeding in the current pregnancy are relevant predictive factors in all women, as are maternal age, cervical length, and fFN in women without PPROM and nulliparity, history of preterm birth in women with PPROM.